The president's ladies : Jane Wyman and Nancy Davis - Dick, Bernard F. (Jackson : University Press of Mississippi, 2014)
"Ronald Reagan, a former actor and one of America's most popular presidents, married not one but two Hollywood actresses. This book is three biographies in one, discovering fascinating connections among Jane Wyman (1917-2007), Ronald Reagan (1911-2004), and Nancy Davis (b. 1921). Jane Wyman, who married Reagan in 1940 and divorced him seven years later, knew an early life of privation. She gravitated to the movies and made her debut at fifteen as an unbilled member of the chorus, then toiled as an extra for four years until she finally received billing. She proved herself as a dramatic actress in The Lost Weekend, and the following year, she was nominated for an Oscar for The Yearling and soon won for her performance in Johnny Belinda, in which she did not speak a single line. Other Oscar nominations followed, along with a Golden Globe for her portrayal of Angela Channing in Falcon Crest. Conversely, Nancy Davis led a relatively charmed life, the daughter of an actress and the stepdaughter of a neurosurgeon. Surrounded by her mother's friends--Walter Huston, Spencer Tracy, Katharine Hepburn, Lillian Gish, and Alla Nazimova, her godmother--Davis started in the theater, then moved on to Hollywood, where she enjoyed modest success, and finally began working in television. When she married Reagan in 1952, she unwittingly married into politics, eventually leaving acting to concentrate on being the wife of the governor of California, and then the wife of the president of the United States. In her way, Davis played her greatest role as Reagan's friend, confidante, and adviser in life and in politics. This book considers three actors who left an indelible mark on both popular and political culture for more than fifty years"--
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 24, 2014).
Master record variable field(s) change: 600
Keywords: Wyman, Jane, -- 1917-2007.; Reagan, Nancy, -- 1921-2016.; Reagan, Ronald; Wyman, Jane, -- 1917-2007.; Reagan, Nancy, -- 1921-; Reagan, Ronald; Reagan, Nancy, -- 1921-2016; Reagan, Ronald; Wyman, Jane, -- 1917-2007.; Motion picture actors and actresses -- United States -- Biography; Presidents' spouses -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture actors and actresses; Presidents' spouses; United States; Electronic books; Biography